Metabolic analysis of glucose, pyruvate, and glutamine in dog oocytes collected from different sized follicles and matured in vitro - Wesselowski, Sonya (Kansas State University, 2008)
Current in vitro maturation (IVM) systems for domestic dog oocytes are inefficient, largely due to the species' unique reproductive physiology. The size of donor follicle influences developmental competence of dog ovarian oocytes. Specifically, oocytes from follicles > 2 mm in diameter complete in vitro nuclear maturation at a higher rate than those from smaller follicles. The objective was to determine the influences of follicular size, maturation time, and meiotic status on oocyte metabolism. We hypothesized that metabolic patterns differed between oocytes from small versus large follicles. Oocytes (n = 531) from adult ovaries were collected and grouped based on follicular size (small, < 1 mm, n = 252; medium, 1 to 2 mm, n = 231; and large, > 2 mm, n = 48). Oocytes were cultured for 0, 24, or 48 hours at 38.5°C in 5% CO[subscript]2 in 80 [Mu]L of TCM 199 + 25[Mu]M [Beta]- mercaptoethanol + 10 ng/ml epidermal growth factor + 0.25 mM pyruvate + 2.0 mM glutamine + 0.1% polyvinyl alcohol + 0.03 mg/ml streptomycin + 0.03 mg/ml penicillin G sodium (IVM medium), assessed for metabolism and evaluated for nuclear status. For metabolic assessments, oocytes were incubated for 3 h in 3 [Mu]l of IVM medium containing (1) 0.005 mM [0.064 [Mu]Ci/[Mu]l] D-53H-glucose (glycolysis) + 1 mM D-614C [0.053 [Mu]Ci/[Mu]l] glucose (glucose oxidation) or (2) 0.001 mM [0.041 [Mu]Ci/[Mu]l] L-G-3H-glutamine + 1 mM [0.027 [Mu]Ci/[Mu}l] 1-14C pyruvate, placed on the lid of a centrifuge tube containing 25 mM NaHCO3 and trapped radioactivity was measured using a [Beta]-counter. Only oocytes at an appropriate meiotic stage for each culture period (n = 380) were included in data analysis (e.g., germinal vesicle stage at 24 and 48 h culture were excluded). Differences in metabolism among groups were analyzed by ANOVA (main effects being follicular class, culture interval, and meiotic status). Oocytes recovered from large follicles metabolized significantly more pyruvate, glutamine, and glucose (via glycolysis) than those from small ones (p < 0.05). Across meiotic stages and follicular sizes, glycolytic rate was lowest in oocytes cultured for 24 hours (p < 0.05) compared to 0 or 48 hours. Metaphase II oocytes had a significantly higher glycolytic rate than those at other meiotic stages (p < 0.05). At culture onset (0 h), oocytes from small follicles predominately used pyruvate (p < 0.05), while oocytes from larger follicles (p < 0.05) predominately metabolized glucose. The present data suggests that dog oocytes preferentially use glucose as an energy substrate and that increasing glycolytic rate correlates with meiotic maturation. In addition, oocytes collected from large follicles exhibit increased metabolic capabilities that may be responsible for their increased developmental competence during IVM.
Keywords: Canine oocyte; Nuclear maturation; Energy substrate; Metabolism; Biology, Molecular (0307)